Olfactory marker protein mRNA is found in axons of olfactory receptor neurons - Wensley, CH (J Neurosci, 1995)
The separation between the cell bodies of olfactory receptor neurons in the nasal cavity and their axon terminals in the olfactory bulb make them attractive for studying axonal transport. Although high molecular weight RNAs are generally believed to be excluded from axons of mature neurons, we demonstrate here that mRNA for olfactory marker protein (OMP), an abundant cytoplasmic protein selectively expressed in mature receptor cells, is present in rodent olfactory receptor axons. OMP RNA was detected by in situ hybridization at the light microscope level in axons and in terminals. By nuclease protection, the level of OMP RNA in the olfactory bulb was 5–10% of that in the olfactory epithelium where the cell bodies reside. In contrast to axonally transported vasopressin and oxytocin mRNAs, which are deficient in their 3′ polyA tails, axonal OMP RNA fractionated as polyA+. OMP RNA was lost from axons and terminals after deafferentation, suggesting that OMP RNA was synthesized in receptor cell bodies in the epithelium and was transported into axons and terminals in the olfactory bulb. RNA for G(olf), a G-protein highly expressed in dendrites of mature olfactory receptor neurons, was not detected in the olfactory bulb. We hypothesize that the immature nature of the cytoskeleton and, specifically, the lack of tightly bundled microtubules allows transport of particular mRNAs in olfactory receptor axons.